2020
DOI: 10.3389/fpsyg.2020.01000
|View full text |Cite
|
Sign up to set email alerts
|

Creative Flow and Physiologic States in Dancers During Performance

Abstract: Pre-professional and professional dancers (n = 60) participated in this ambulatory psychophysiology study that investigated performance flow and heart rate and autonomic nervous system (ANS) function during three time periods: baseline rest, performance, and post-performance rest. To gather these results, the psychophysiology laboratory traveled to the concert hall to collect data on dancers. The self-report Flow State Scale (FSS) measured global flow, challenge-skill balance, sense of control, and autotelic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…That is, the PEP model explains just 7% of the variance in flow ( R 2 = .07). Even though the size of this effect is comparable to similar effects reported in the literature (Jaque et al, 2020), future work, in more applied contexts, should provide more clarity about the practical relevance of the relations between physiological synchrony, flow, and performance.…”
Section: Discussionsupporting
confidence: 79%
“…That is, the PEP model explains just 7% of the variance in flow ( R 2 = .07). Even though the size of this effect is comparable to similar effects reported in the literature (Jaque et al, 2020), future work, in more applied contexts, should provide more clarity about the practical relevance of the relations between physiological synchrony, flow, and performance.…”
Section: Discussionsupporting
confidence: 79%
“…The decision to compare the subjective experience of the creative process and dispositional/state flow experiences was based on research that demonstrated that dancers value creativity based on the process more than the product (Clements & Redding, 2020). Dancers also reported experiencing flow states while performing, including heightened frequency (dispositional) of experiencing many of the nine flow dimensions (Jaque et al., 2020; Thomson & Jaque, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the performance arts, similar conclusions have been reached regarding flow and ultimate performance. In a study by Jaque et al [19], preprofessional and professional dancers endorsed moderate-to-high-flow states associated with creative experiences, rather than challenge-skill scenarios as with traditional athletes; further, the flow experience was significantly amplified in the concert hall. Additionally, elite musicians were more likely to experience a transformation of time and more profound autotelic experiences compared with athletes, while athletes were more likely to have clear goals with unambiguous feedback [19,20 ▪ ].…”
Section: Flow In Literaturementioning
confidence: 96%
“…In a study by Jaque et al [19], preprofessional and professional dancers endorsed moderate-to-high-flow states associated with creative experiences, rather than challenge-skill scenarios as with traditional athletes; further, the flow experience was significantly amplified in the concert hall. Additionally, elite musicians were more likely to experience a transformation of time and more profound autotelic experiences compared with athletes, while athletes were more likely to have clear goals with unambiguous feedback [19,20 ▪ ]. Consider the environment itself in which the individual is working: an athlete's home-field, linked to the well proved theory of home-field advantage, is a very different atmosphere from the dancers’ concert hall.…”
Section: Flow In Literaturementioning
confidence: 96%